Correction: Mariaccia et al. Impact of Polar Vortex Modes on Winter Weather Patterns in the Northern Hemisphere. Atmosphere 2024, 15, 1062 - Alexis Mariaccia; Philippe Keckhut; Alain Hauchecorne (Atmosphere)
In the original publication [...]